KONSEP PENDIDIKAN PERSPEKTIF IBNU JAMAâ€™AH (TELAAH TERHADAP ETIKA GURU DALAM KEGIATAN BELAJAR MENGAJAR) - Junaidi Arsyad; Maisaroh Ritonga; Syamsu Nahar (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
Badruddin Muhammad Ibn Ibrahim Ibn Sa'ad Allah Ibn Jama'ah Shakhr Ibn Ibn Hazim Abd Allah ibn al-Kinany or distinguished by Ibn Jamaah is one of the leaders of Islamic education who have brilliant ideas. Thought studies listed in his book al-Sami Tadzkirat wa al-Mutakallim fi Adab wa al-Alim al-Muta'allim. Thought education is very relevant to today's modern education, one of which is on ethics for teachers in the learning process. One of his thoughts on the ethics of teachers was that a teacher should not be dependent on the results of the teaching profession. This is because science is taught by a teacher is very precious so it is not worth doing. This Research will be focused on the notion of Ibn Jama'ah concerning the ethics teacher. This problem is interesting to study because of the current problems faced by teachers are increasingly complex. The method used is qualitatively using content analysis to analyze how the ideas of Ibn Jamaah regarding this. This research included a literature review that examines the book he wrote. This study shows that thinking about ethics teacher by Ibn Jama'ah according to very relevant to modern education such as the need for teachers to have a consistent attitude, boost performance for work (dynamic), love science, forward to obtain excellent generation, and so forth.Â Kata kunci: Ibn Jamaah, etika guru, pendidikan Islam